Baumol's cost disease and the sustainability of the welfare state - Torben Andersen; Claus Thustrup Kreiner (University of Copenhagen, Economic Policy Research Unit (EPRU), 2015)
If productivity increases more slowly for services than for manufactured goods then services suffer from Baumol's cost disease and tend to become relatively more costly over time. Since the welfare state in all countries is an important supplier of tax financed services, this translates into a financial pressure which seems to leave policymakers with a trilemma; increase taxes (and hence tax distortions), cut spending or redistribute less. Under the assumptions underlying Baumol's cost disease, we show that these dismal implications are not warranted. The welfare state is sustainable and Baumol growth leaves scope for Pareto improvements.
Keywords: 330